Nitrous Oxide Levels In Operating and Recovery Rooms of Iranian Hospitals - Sh Sadigh Maroufi; MJ Gharavi; M Behnam; A Samadikuchaksaraei (Tehran University of Medical Sciences, 2011)
"nBackground: Nitrous oxide (N2O) is the oldest anesthetic in routine clinical use and its occupational exposure is under regulation by many countries. As studies are lacking to demonstrate the status of nitrous oxide levels in operating and recovery rooms of Iranian hospitals, we aimed to study its level in teaching hospitals of Tehran University of Medical Sciences."nMethods: During a 6-month period, we have measured the shift-long time weighted average concentration of N2O in 43 operating and 12 recovery rooms of teaching hospitals of Tehran University of Medical Sciences."nResults: The results show that the level of nitrous oxide in all hospitals is higher than the limits set by different countries and anesthetists are at higher risk of exposure. In addition, it was shown that installation of air ventilation could reduce not only the overall exposure level, but also the level of exposure of anesthetists in comparison with other personnel."nConclusion: The high nitrous oxide level in Iranian hospitals necessitates improvement of waste gas evacuation systems and regular monitoring to bring the concentration of this gas into the safe level.